PENGARUH METODE EKSTRAKSI TERHADAP AKTIVITAS ANTIMIKROBA EKSTRAK METANOL DAUN MIMBA (Azadirachta indica Juss) - Handayany, Gemy Nastity (Teknosains: Media Informasi Sains dan Teknologi, 2016)
An investigation of the influence of extraction method on the antimicrobial activity of methanol extract of leaves of neem (Azhadirachta indica Juss) against multiple microbes. This study aims to determine the extraction method that produces extracts that can provide the best antimicrobial activity. Extraction methods used include maceration, soxhletasi, and reflux using methanol solvent. Tests conducted by inhibition screening test, the maceration method inhibits Staphylococcus aurus, thyposa Salmonella, Staphylococcus epidermidis, Streptococcus mutans, Vibrio sp, Escherichia coli, Bacillus Subtilis and Pseudomonas aeroginosa, whereas Staphylococcus aurus soxhlet method, thyposa Salmonella, Staphylococcus epidermidis, Streptococcus mutans, Vibrio sp, Escherichia coli, and Pseudomonas aeroginosa, and reflux methods aurus Staphylococcus, Staphylococcus epidermidis, Vibrio sp, Escherichia coli and Pseudomonas aeroginosa. Minimum inhibitory concentration test, the methods of maceration, soxhlet and reflux in a row that the bacterium Escherichia coli to produce 0.05%, 0.1%, and 0.2%, while the bacterium Staphylococcus aureus, 0.05%, 0.2% and 0.2%. Minimum kill concentration test, the methods of maceration, reflux, and Soxhlet, respectively, namely the bacterium Escherichia coli and Staphylococcus aureus produce 0.2%, 0.4% and 0.4%. Test medium agar diffusion method using Glucose Nutrient Agar (GNA). Antimicrobial activity test results show that the largest amount of inhibition zone on the test bacteria Escherichia coli and Staphylococcus aureus maceration method.